Effects Of Keratin-Gelatin And Basic Fibroblast Growth Factor-Gelatin Composite Film On Open Wound Healing In Dogs And Cats - Jothi. N, Arul (2007)

(untitled)
Wound is a disruption of the normal continuity of the skin surface. A prolonged wound healing time is distressing and expensive. Immediate wound coverage is a cornerstone of wound management. Extensive wounds in the skin can be treated using dressing materials and skin grafts. A full-thickness mesh graft can be applied to cover large skin defects. To accelerate wound healing, the use of biomaterials such as keratin, gelatin and basic fibroblast growth factor (bFGF) has increased in recent years. Feathers contain beta keratin as a major component. Keratin as a structural protein that can be processed from poultry feathers and made into value added products, which benefit wounds healing. Gelatin and bFGF are well known for their wound healing properties. Dermal substitutes are very expensive and used routinely in human. However such materials are not available at reasonable cost to treat extensive wounds in animals.Keratin hydrolysates from poultry feathers were prepared by controlled alkaline hydrolysis. Following hydrolysis the supernatant solution was decanted and brought to pH 7.0 using sulfuric acid, then 10% solution of pharmaceutical grade gelatin solution was mixed followed by addition of 1% ethylene glycol and 0.35% glutaraldehyde to the solution and finally cast in polythene trays and dried at 50 0C. bFGF-gelatin composite film was prepared by adding pharmaceutical grade gelatin solution 10 %, 1% ethylene glycol and 0.35% glutaraldehyde to basic fibroblast growth factor (0.015μg/cm2) and casted in polythene trays and dried at 50 0C. The film was soaked for 2 minutes in gentamycin (Dutch farm Veterinary pharmaceuticals, Netherlands) and then applied on wound. This study was conducted with hypothesis that keratin-gelatin and bFGF-gelatin composite films are effective wound healing stimulants causing early re-epithelialization and an uncomplicated wound healing favoring early acceptance of the full thickness skin mesh. The objectives of this study was to identify and evaluate wound healing properties of keratin-gelatin and bFGF-gelatin composite films on open wound and as a feeder layer for early acceptance of full-thickness skin mesh graft in dogs. Following the identification of the better of the two biomaterials, it was used in clinical cases involving 10 cats and two dogs with extensive skin wounds presented to the University Veterinary Hospital University Putra Malaysia. The application of keratin and bFGF on wound healing in experimental dogs and clinical cases in this research was a pilot study undertaken. Thirty six healthy dogs were used in the study. Under general anaesthesia and aseptic condition, a full-thickness skin wound (approximately 5x 5cm) was created lateral to the right loin region. Eighteen animals were used for open wound groups divided into 3 groups (n = 6) namely Group I (control group), Group II (treated with keratin-gelatin composite film) and Group III (treated with bFGF-gelatin composite film). Another 18 animals were treated with full-thickness skin mesh graft were also divided into 3 Groups (n = 6) namely Group I (control group), Group II (treated with feeder layer of keratin-gelatin composite film), Group III (treated with feeder layer of bFGF-gelatin composite film). Evaluation of the effect of biomaterials on open wound and the full-thickness skin mesh graft was done based on clinical observation, haematological, bacteriological, biochemical and histopathological examinations on Days 4, 8, 12, 16 and 20 post-operation. Biochemical and histopathological evaluations on the full-thickness skin mesh graft were done on Days 12, 16 and 20 post-operation. The keratin-gelatin and bFGF-gelatin composite films could easily be applied on wounds. The composite films were well accepted and tolerated by animals and did not show any adverse reactions. Open wounds treated with keratin-gelatin (Group II) showed a bright red granulation tissue, without malodour and exudates on Day 20 post-operation, when compared to other groups. The percentage of wound epithelialization, wound contraction and total wound healing was significantly higher (P<0.05) in keratin-gelatin (Group II) throughout the trail. The full-thickness skin mesh graft treated with keratin-gelatin (Group II) as a feeder layer showed an early vascularization of the graft, with epithelialization of the interstices. Acceptance of the graft by Day 12 post-operation was complete with hair growth and normal colour of the skin without any evidence of rejection. The graft acceptance was 90-100% on Day 20 post-operation. In bFGF-gelatin (Group III), all animals showed a dark discolouration of epidermis of the graft without rejection on Days 16 and 20 post-operation. No adverse effects were observed on the hematological values obtained in the treated groups. On bacteriological examination, Staphylococcus aureus, Klebsiella spp., Proteus spp. and Pseudomonas spp. were isolated in all animals in open wound groups. Staphylococcus aureus was isolated from one animal each in Groups I and II and Proteus spp. from one animal in Group III treated with the full-thickness skin mesh graft. The keratin-gelatin composite film (Group II) favoured tissue DNA, protein and collagen formation, which was essential for wound healing and early acceptance of the full-thickness skin mesh graft. The efficiency of fibroblast formation and angiogenesis was good in the animals treated with keratin-gelatin composite film (Group II) which favoured an early wound healing. In the full-thickness skin mesh graft group, the animals treated with feeder layer of keratin-gelatin composite films, showed normal epidermis thickness on Day 20 post-operation. Keratin-gelatin composite film was effective in clinical cases involving 10 cats and 2 dogs presented at the University Teaching Hospital of Universiti Putra Malaysia. As per the hypothesis, Keratin-gelatin composite film was an effective wound healing stimulant causing early re-epithelialization and uncomplicated wound healing favoring an early acceptance of the full thickness skin mesh graft. The objective of this study was fulfilled when the use of keratin-gelatin composite film was found to be a better biomaterial when compared to bFGF-gelatin composite film. Keratin-gelatin was effective for wound healing in clinical cases presented at the University Teaching Hospital of Universiti Putra Malaysia. The above findings have a commercial application because keratin from poultry feathers an inexpensive as a skin substitute to stimulate wound healing in animals where the cost of treatment is a major consideration by clients. Further research is needed at different concentrations of keratin-gelatin and bFGF-gelatin incorporated composite film for wound healing in experimental and clinical cases. vii